Overcoming Barriers to Halal Certification: A Study of SMEs in Indonesia’s Food Industry - Kholid Albar; Nasrullah Bin Sapa; Cut Muthiadin (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
This study examines the challenges and opportunities associated with halal certification for small and medium-sized enterprises (SMEs) in Indonesia’s food industry. The objective is to explore how SMEs perceive and navigate the halal certification process, as well as the role of government initiatives and technological tools in overcoming barriers to certification. The research employs a qualitative methodology, using semi-structured interviews and case studies to gather data from SMEs, certification bodies, and government officials. Thematic analysis is applied to identify key themes related to the challenges, such as a lack of understanding and the high costs of certification, as well as the support provided by government programs like SEHATI (Free Halal Certification) and the use of digital tools in streamlining the process. The findings indicate that while SMEs face significant barriers in obtaining halal certification, including financial constraints and knowledge gaps, government support and technological innovations play a crucial role in facilitating access to certification. Halal certification is shown to improve the competitiveness of SMEs by enhancing product quality, fostering consumer trust, and opening access to global markets. Additionally, it promotes sustainable and ethical production practices. The study contributes to the understanding of halal certification’s impact on SMEs, highlighting the need for continued collaboration between stakeholders. It suggests further research into the long-term effects of halal certification on SMEs’ financial performance and the role of digital tools in simplifying certification processes.